Influence of sensory information on static balance in older patients with vestibular disorder - Macedo,Camila (2015)
Introduction: With aging, the sensory systems suffer an accumulation of degenerative, infectious and/or traumatic processes that may hinder the body balance maintenance. Objective: To assess the influence of sensory information on static body balance of elderly individuals with vestibular disorders. Methods: Cross-sectional study of elderly individuals with vestibular disorders. The Clinical Test of Sensory Interaction and Balance and posturography integrated with virtual reality (Balance Rehabilitation UnitTM) were used. Posturography parameters analyzed included center of pressure and velocity of body sway. Results: 123 individuals with mean age of 73.11 were assessed. Worst performance was observed in the Clinical Test of Sensory Interaction and Balance condition of visual dome-unstable surface. Differences between conditions were: firm surface-open eyes/firm surface-closed eyes, unstable surface-open eyes/unstable surface-closed eyes (p < 0.001), and unstable surface-closed eyes/unstable surface-visual dome. Considering center of pressure and velocity of body sway, significant differences were observed between the following conditions: firm surface-open eyes/firm surface-closed eyes: firm surface-saccadic stimulus/firm surfacevertical optokinetic stimulus; firm surface-optokinetic stimuli/firm surface-visual-vestibular interaction; and firm surface-visual-vestibular interaction/unstable surface. Worse performances were observed in conditions firm surface-closed eyes, firm surface-vertical optokinetic stimulus, F-visual-vestibular interaction, and unstable surface-closed eyes. There was a difference in the center of pressure between firm surface-closed eyes/firm surface-saccadic stimulus, with a worse performance in the condition of firm surface-closed eyes, and of velocity of body sway, between firm surface-saccadic stimulus/firm surface-horizontal optokinetic stimulus (p < 0.001). Conclusion: Static body balance in elderly individuals with vestibular disorders is worse when the sensory conditions are more challenging, i.e. stable and unstable surfaces, visual stimuli, such as optokinetic and visual-vestibular interaction, and with the eyes closed.